Emotional Vulnerability and Eating Scripts: Towards a Personalized Approach in Binge Eating Correction - Sinkevych, Інна (Psychosomatic Medicine and General Practice, 2024)
Relevance. Within the structure of eating disorders, binge eating disorder (BED) stands out as a clinically significant form, demonstrating a close association with emotional dysregulation, high levels of alexithymia, and deficits in emotional intelligence. Of particular interest is its association with chronic somatic pain, which not only co-occurs with BED but is also shaped by shared mechanisms of psycho-emotional dysregulation. At the same time, unified models of the psychosocial pathogenesis of BED remain fragmented, complicating the development of effective personalized intervention programs.. Objective. To identify the emotional and social factors associated with the severity of binge eating manifestations depending on the premorbid type of eating behavior, with the aim of developing targeted medical and psychological correction strategies. Methods and Materials. The study included 163 patients with BED. BES, HADS, TAS-20, and Hall’s Emotional Intelligence Test were used. Premorbid eating behavior was categorized as emotional, compulsive, or situational. Correlation and regression analyses were performed to determine associations between psychosocial factors and BED severity. Results. Significant relationships were found between emotional state, alexithymia, emotional intelligence, and BED severity. Gender-specific emotional responses and eating behavior types modified these correlations. Patients with compulsive eating showed the lowest levels of emotional intelligence and the highest anxiety and depression scores. Quality of life significantly deteriorated under conditions of high BMI, alexithymia, and emotional maladjustment. Conclusions. Premorbid psychosocial patterns of eating behavior are relevant targets for personalized psychotherapeutic interventions in BED. Accounting for individual affective functioning and social context allows more effective modification of behavioral patterns and improved quality of life in patients.